Respuesta :

Answer:

3 sips equal a gulp

Step-by-step explanation:

we have

[tex]5sips+4gulps=1glass[/tex] ----> equation A

[tex]13sips+7gulps=2glass[/tex]

Divide by 2 both sides

[tex]6.5sips+3.5gulps=1glass[/tex] ----> equation B

equate equation A and equation B

[tex]5sips+4gulps=6.5sips+3.5gulps[/tex]

Group terms that contain the same variable

[tex]4gulps-3.5gulps=6.5sips-5sips[/tex]

[tex]0.5gulps=1.5sips[/tex]

[tex]gulps=(1.5/0.5)sips[/tex]

[tex]gulps=3sips[/tex]

therefore

3 sips equal a gulp